Huquq Al-Mirath Linaqil Al-Adwa Bi Fairus Kuruna (Kufid-19) Fi Manzur Al-Shari’ah Al-Islamiyah Wa Al-Qanun Al-Indunisiyi - Azziz Bachir Raouane; Ruhi Fadzlyana Jailani; Fajar Rachmadhani; Mualimin Mochammad Sahid (Postgraduate Program (PPs) and the Institute for the Study of Religion and Society (LSAS), 2024)
Vol 15, No 2